Cationic Metal–Organic Framework-Based Mixed-Matrix Membranes for Fast Sensing and Removal of Cr2O72− Within Water - Zhang, Shuyun; Zheng, Heqi; Yang, Yu; Qian, Guodong; Cui, Yuanjing (Frontiers in Chemistry, 2022)
Considering that metal-organic framework (MOF)-polymer mixed-matrix membranes (MMMs) can overcome the drawbacks of intrinsic fragility and poor processability of pure-MOF membranes, we design a MOF-based MMMs for efficient removal and fast fluorescence sensing of heavily toxic ions within water systems simultaneously. In this work, a series of MOF-based MMMs are prepared by mixing a hydrolytically stable cationic [Eu7(mtb)5(H2O)16]·NO3·8DMA·18H2O (denoted as Eu-mtb) MOF material into poly(vinylidene fluoride) with high loadings up to 70%. The free volume at the interface between polymer and Eu-mtb particles, combined with the permanent porosity and uniform distribution of Eu-mtb particles enable these MMMs to show fast enrichment of Cr2O72- from solutions and consequently have a full contact between the analyte and MOFs. The developed Eu-mtb MMM (70 wt% loading) thus shows both efficient removal and exceptional fluorescent sensing of Cr2O72- in aqueous media. The overall adsorption capacity of Eu-mtb MMM (70 wt% loading) for Cr2O72- reaches up to 33.34 mg/g, which is 3.4 times that of powder-form Eu-mtb. The detection limit of Eu-mtb MMM (70 wt% loading) for Cr2O72- is around 5.73 nM, which is lower than that of the reported powder-form Eu-mtb. This work demonstrates that it is feasible to develop flexible luminescent MOF-based MMMs as a significant platform for efficient removal and sensitive sensing of pollutants from water systems simultaneously.